Analisis Radiography dan Macro Structure Baja Karbon EH36 dengan Grade A Terhadap Hasil Pengelasan FCAW Variasi Ampere - widodo, risriki; Purwanto; Siswadi (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
Ship superstructure or commonly called superstructure in welding fabrication found problems arising from the welding process. Problems caused by welding such as defects on the surface of the weld and defects in the weld. Defects inside the weld require radiography and macro structure testing to see indications that arise such as porosity, slag inclusion and incomplete fusion. The purpose of this research is to determine the results of Flux Cored Arc Welding (FCAW) between Grade EH36 carbon steel material and Grade A with V Groove connection type and for backing material using ceramic strip without gouging. The research process that has been carried out includes welding the two materials with the Flux Cored Arc Welding (FCAW) method using parameters 160 A, 200 A and 250 A. Non Destructive Test (NDT) testing used is Radiography Test while Destructive Test (DT) testing is Macro Structure Test, both of which aim to find indications of defects in the weld. The conclusions found after the Radiography and Macro Structure tests were found no indication of defects in the weld metal at parameter variations of 160 Ampere, 200 Ampere and 250 Ampere.